Thomas Fitzpatrick – Gunsmith of Dublin. (2nd July 2016) - Godwin, Brian
Abstract : Knowledge of early Dublin gunmakers is limited, mainly due to the destruction of records during the Civil War of the 1920s. This article focuses on an early pair of rifled turn-off pistols by Thomas Fitzpatrick and presents new research recently carried out by the author on this little-known gunmaker.